The unknown life of Jesus Christ - Notovitch, Nicolas, 1858- (Salt Lake City, UT : Project Gutenberg, 2009)
"The Unknown Life of Jesus Christ" by Nicolas Notovitch is a historical account written in the late 19th century. The book explores the lesser-known aspects of Jesus Christ's life, particularly focusing on Notovitch's travels in Tibet, where he claims to have discovered ancient texts about Jesus. The author delves into these chronicles to shed light on the life of Jesus from a perspective not typically found in Christian teachings. At the start of the narrative, Notovitch recounts his travels across the Orient, specifically his journey to Tibet during 1887, driven by a quest for knowledge about ancient manuscripts concerning Jesus. He shares his encounters with Buddhist monks who tell him about significant texts archived in Lhasa that discuss the life of Jesus, referred to by them as "Issa." As he continues his journey through mountainous regions and villages, he experiences various cultural and religious practices that draw parallels between Buddhism and Christianity, hinting at a deep exploration of the spiritual connections between the two religions. This opening portion sets up Notovitch$1 (Bs investigation into the life and teachings of Jesus as seen through the lens of Tibetan Buddhism and promises an intriguing account of his findings. (This is an automatically generated summary.)s
Release date is 2009-07-01
E-text prepared by David Edwards, Paul Motsuk, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Jesus Christ -- Biography -- Apocryphal and legendary literature; Christianity and other religions -- Buddhism